Multiple interaction nodes define the postreplication repair response to UV‐induced DNA damage that is defective in melanomas and correlated with UV signature mutation load. Issue 1 (19th December 2019) - Pavey, Sandra; Pinder, Alex; Fernando, Winnie; D'Arcy, Nicholas; Matigian, Nicholas; Skalamera, Dubravka; Lê Cao, Kim‐Anh; Loo‐Oey, Dorothy; Hill, Michelle M.; Stark, Mitchell; Kimlin, Michael; Burgess, Andrew; et al.
Abstract : Ultraviolet radiation‐induced DNA mutations are a primary environmental driver of melanoma. The reason for this very high level of unrepaired DNA lesions leading to these mutations is still poorly understood. The primary DNA repair mechanism for UV‐induced lesions, that is, the nucleotide excision repair pathway, appears intact in most melanomas. We have previously reported a postreplication repair mechanism that is commonly defective in melanoma cell lines. Here we have used a genome‐wide approach to identify the components of this postreplication repair mechanism. We have used differential transcript polysome loading to identify transcripts that are associated with UV response, and then functionally assessed these to identify novel components of this repair and cell cycle checkpoint network. We have identified multiple interaction nodes, including global genomic nucleotide excision repair and homologous recombination repair, and previously unexpected MASTL pathway, as components of the response. Finally, we have used bioinformatics to assess the contribution of dysregulated expression of these pathways to the UV signature mutation load of a large melanoma cohort. We show that dysregulation of the pathway, especially the DNA damage repair components, are significant contributors to UV mutation load, and that dysregulation of the MASTL pathway appears to be a significant contributor to high UV signature mutation load. Abstract : The UV‐G2 checkpoint is triggered by UV‐induced DNA lesions not repaired by NER during G1 phase. Global genomic NER (GG‐NER) pathway repairs these lesions during G2 phase, and homologous recombination repair (HRR) repairs the single‐stranded gaps. The MASTL pathway controls exit from the checkpoint arrest. These are all under AKT‐dependent translational control.